Non-renewable and renewable energy consumption and CO2 emissions in OECD countries: A comparative analysis - Shafiei, S.; Salim, Ruhul (Elsevier Science Ltd., 2014)
This paper attempts to explore the determinants of CO2 emissions using the STIRPAT model and data from 1980 to 2011 for OECD countries. The empirical results show that non-renewable energy consumption increases CO2 emissions, whereas renewable energy consumption decreases CO2 emissions. Further, the results support the existence of an environmental Kuznets curve between urbanisation and CO2 emissions, implying that at higher levels of urbanisation, the environmental impact decreases. Therefore, the overall evidence suggests that policy makers should focus on urban planning as well as clean energy development to make substantial contributions to both reducing non-renewable energy use and mitigating climate change.